1999
DOI: 10.1093/humrep/14.11.2851
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endometrial volume by three-dimensional ultrasound prior to embryo transfer: clues to endometrial receptivity

Abstract: The aim of the present prospective study was to obtain quantitative data on endometrial volume by three-dimensional (3D) ultrasound at the time of embryo transfer in an in-vitro fertilization programme and to assess its value in predicting endometrial receptivity. The cycles (n = 72) were classified according to endometrial volume: group A <2 ml, group B 2-4 ml, and group C >4 ml. Comparisons of the groups showed that pregnancy and implantation rates were significantly lower (P < 0.05) in the group of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 34 publications
6
80
1
2
Order By: Relevance
“…Two parameters are considered to predict pregnancy: a) endometrial volume and b) (sub) endometrial flow. a) The first studies reported a good correlation between endometrial volume and pregnancy (31)(32)(33). Although it has been shown that the endometrium must attain at least 2.0-2.5 ml to achieve a pregnancy, recent studies did not confirm the relation between endometrial volume and pregnancy outcome (33)(34)(35)(36)(37).…”
Section: Endometrial Receptivitymentioning
confidence: 99%
“…Two parameters are considered to predict pregnancy: a) endometrial volume and b) (sub) endometrial flow. a) The first studies reported a good correlation between endometrial volume and pregnancy (31)(32)(33). Although it has been shown that the endometrium must attain at least 2.0-2.5 ml to achieve a pregnancy, recent studies did not confirm the relation between endometrial volume and pregnancy outcome (33)(34)(35)(36)(37).…”
Section: Endometrial Receptivitymentioning
confidence: 99%
“…They found that endometrial volume failed to predict outcome of IVF and that estradiol levels did not correlate with endometrial volume. Almost simultaneously, Raga et al (1999) reported on 72 patients who underwent IVF cycle, using the same technique that Schild et al (1999) for calculating endometrial volume but ultrasound examination was performed on the day of embryo transfer. These authors found that pregnancy rate was significantly lower (15%) if endometrial volume was < 2 ml than if it was > 2 ml (34.5%).…”
Section: Endometrial Volumementioning
confidence: 99%
“…48 Studies by Schild et al 49 and Yaman et al 50 showed no significant differences between endometrial thickness/ endometrial volume measurements in patients who conceived compared to those who did not, however did suggest a minimal volume of 2.0 to 2.5 cm³ was required for implantation to occur. This concept is supported by Raga et al 51 who assessed endometrial volume in seventy-two women on the day of embryo transfer and noted that no pregnancies occurred in patients with an endometrial volume below 1 cm³ and that implantation rates were significantly lower when the endometrial volume was less than 2cm³. It is uncertain if volume measurements provide more predictive information than standard two-dimensional measures of endometrial thickness as this has not been thoroughly assessed in randomised, blinded trials.…”
Section: Endometrial Receptivitymentioning
confidence: 99%